PROTOTYPE DESIGN OF PARKING SLOT AVAILABILITY INFORMATION SYSTEM USING ARDUINO UNO AT NABIRE AIRPORT CENTRAL PAPUA - demianus yogi; Sofyan; Zulkarnin (Journal of Pedagogical Content Knowledge, 2025)
The increasing number of vehicles and limited transportation infrastructure are common problems at Nabire Airport, Central Papua Province. In the current parking area monitoring process, manual methods are still used to determine the number and availability of capacity in the parking area. The research process is carried out in several ways, such as recording the number of vehicles entering and directly observing the condition of the vehicles that are parked. The method of developing a parking slot availability information system using Arduino Uno at Nabire Airport, Central Papua Province, will follow an adaptive and responsive software development approach. The system development method used is the incremental model. This model was chosen because it allows for gradual system development, allowing for the addition of features iteratively based on user needs and feedback in the Purpose of Designing a Prototype of a Parking Slot Availability Information System Reducing Waiting Time Minimizing in Improving User Experience to Provide comfort and satisfaction to users by simplifying the Nabire Airport parking process 1.Optimizing Parking Slot Usage: Helping in better parking slot management.